Analisis Postur Kerja Operator pada Area Pengantongan Pupuk Mengunakan Metode OWAS di PT. Pupuk Iskandar Muda - Sofiyanurriyanti, Sofiyanurriyanti; Ardiyansyah, Agus; Rahayu, Cut Apriani (Jurnal Optimalisasi, 2020)
This research was conducted at PT. Pupuk Iskandar Muda is located on Jalan Medan-Banda Aceh, Tambon Baroh Village, Dewantara District, North Aceh Regency, Aceh Province. The study was conducted in the distribution department of PT. Pupuk Iskandar Muda in warehouse line I. This study aims to analyze the level of musculoskeletal disorders or muscle disorders in manual handling operators, to determine the level ofÂ  risk ofÂ  musculoskeletal disorders or muscle disorders in manual handling operators, find out the forms of improvement of risks and complaints identified. One method used to analyze work attitudes is the ovako work posture analysis system (OWAS) method. The results of the study on the operator's work posture in the bagging area, there are 4 elements of activities in the fertilizer company, namely filling the fertilizer, folding inner (inside the fertilizer bag), sewing the fertilizer bag, not experiencing interference on the muscle with a value of 1 meaning there is no need for improvement, whereas in the part the preparation of fertilizer to the palette has muscle disorders and there is a complaint with a value of 3 meaning that immediate repair is needed.